Frequência de suínos soropositivos para Salmonella sp. em granjas afetadas em diferentes níveis de severidade pela Síndrome Multissistêmica de Definhamento do Leitão Desmamado - Schwarz, Patrícia; Kich, Jalusa Deon; Coldebella, Arlei; Seyboth, Leonardo; Romeiro, Cherlla; Corbellini, Luis Gustavo; Cardoso, Marisa (Acta Scientiae Veterinariae, 2018)
Background: The Post-weaning Multisystemic Wasting Syndrome (PMWS) has caused considerable losses due to mortality and wasting of pigs and has been often associated with co-infections with other viral or bacterial agents. At the present time, PMWS is the most important infectious disease syndrome in the Brazilian swine production. With a variety of symptoms, this syndrome affects the immune system and can thus open the door for co-infections, which results in performance losses. Positive results of immunohistochemistry for PCV2 in pigs, we obtained the isolation of Salmonella enterica in 36.2% cases, demonstrate that co-infection occurs in Brazilian herds. However, there is still determining whether there is an increase in the number of carriers of Salmonella sp. in swine herds affected by PCV2. From this, the present study aimed to investigate the frequency of animals positive for Salmonella sp. in pig herds with different levels of intensity of involvement by PMWS. Material, Methods and Results: Productive performance data and most prevalent symptoms were investigated in herds associated to 11 Brazilian swine companies that reported the occurrence of PMWS. The production systems, where the presence of S. enterica in pigs had been previously confirmed, was selected. A three-site management system was adopted, with each stage (breeding, nursery and finishing) housed in separate sites. Herds (n=188) were classified according to the mortality and wasting frequency, and these data were considered as PMSW severity degrees. Blood samples were taken from slaughter pigs of each herd and submitted to an indirect ELISA test against Salmonella sp. Statistical analysis was performed using chi-square for linear trend to test the hypothesis of increased proportion of flocks positive for Salmonella with levels of involvement of PMWS, to increase the power of the sample, the variable Salmonella infection was collapsed into d” 70% and>70%. The analysis was performed using the software EpiInfo 6.0. Discussion: The presence of clinical signs consistent with PMWS in herds, coupled with the confirmation from the occurrence of PCV2 in farms associated with the company, was observed in all farms included in the study. The intensity of infection has been associated with increased culling and mortality in herds affected and, therefore, was adopted as a criterion level of involvement of clinical PMWS. In this study the factor was not considered a medical illness, but the level of seroprevalence of Salmonella sp., a rate that has been used as an indicator of prior exposure to this agent and that is a risk factor for the presence of carrier animals asymptomatic slaughter and the contamination of carcasses. Thus, the results indicate that farms that had involvement of more severe PMWS were classified in the prevalence of high-risk (> 70%) for the presence of carriers of Salmonella sp. slaughter. In all companies a decrease on the animal performance was detected and a tendency of a higher frequency of enteric symptoms associated to PMWS was observed. Seroprevalence >70% against Salmonella was associated to higher PMWS severity (P=0.003). This result may be related to the immune impairment caused by PMWS that may predispose to Salmonella infection, as well as to the occurrence of common risk factors to both infections in affected herds. In conclusion, a high frequency of Salmonella carrier pigs may be an additional problem in farms severely affected by PMWS.